Studying on plasma acid using in hemp degumming process - Wang Ying; Yin Di, Ji Yingchao; Zhang Qingli; Yu Zhihua; Li Hong; Wang Qiuhong (Functional Materials, 2016)
The purpose of this study is to provide a green agent for hemp degumming process. In the study, plasma acid was collected by processing distilled water with dielectric barrier discharge device under atmospheric pressure. Then the plasma acid was used in hemp degumming process. The facilities and instruments required in the whole procedure were easy operation and low cost. In this experiment, bath ratio, temperature and processing time were main factors. The optimal scheme of plasma acid degumming process was proposed through orthogonal experiment. The results of the pectin and lignin removal rate tests revealed that plasma acid was effective in hemp degumming process. After plasma acid treatment, the content of pectin and lignin was decreased by 58.553% and 43.70%, respectively. After plasma acid treatment, the cellulose structure of hemp fiber has not been changed by the XRD analysis. Lots of single fibrils were clearly seen in the SEM images.